Fenomena Bullying Peserta Didik Pada Sekolah Menengah Pertama (SMP) - Rozzaqyah, Fadhlina; Tanjung, Romi Fajar; Andriani, Dian Sri; AR, Silvia; Amarullah, Imam Bastoh; Assakdiah, Annisa (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
Bullying is an action carried out with the aim of hurting or harming someone, either through cruel words, social exclusion or physical violence. This behavior can occur in a variety of environments, such as school, work, or even online, and often leaves a deep psychological impact on the victim. This research aims to explore the phenomenon of bullying in junior secondary education. The research method used is descriptive quantitative. Sampling used random sampling techniques and a sample of 100 students at Junior High School (SMP) was obtained. Data collection used the Bullying Behavior Tendency Instrument in Secondary Students. Data analysis uses item analysis, indicators with classification techniques for the level of student bullying behavior using Excel and SPSS. The research results found that indicators of bullying behavior were generally in the very low category and indicators of having experienced bullying were mostly in the very low category, but some were in the very low, medium and high categories. It was then found that there were significant differences in bullying behavior in terms of gender, while there was no difference in the level of bullying received in terms of gender, meaning that the bullying behavior received was relatively the same between men and women.